ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA QUE SE DEDICA A LA GENERACIÓN DE ENERGÍA MEDIANTE LA UTILIZACIÓN DE PANELES SOLARES EN LA CIUDAD DE MACARA; DETERMINACIÓN DEL COSTO Y RENTABILIDAD DEL PROYECTO - Cueva Paucar, Jimmy Xavier (2020)
Companies in the non-financial sector are instruments that promote the growth of a country's economy; through the investment of large capitals; by virtue of this, the Public Limited Companies are part of the non-Financial sector, which are constituted by the desire and economic contribution of their partners, have a social purpose, and base their vision and commitment on the advancement and common welfare of their partners. The purpose of this investment project is to determine, through a feasibility study, the market, technical, administrative-legal and economic-financial study, and at the same time establish the cost and profitability for the creation of a company dedicated to the generation of energy through the use of solar panels in the city of Macará, determining the general objective mentioned above, then the specific objectives are applied. Carry out a market, technical, administrative-legal, Economic-Financial study for the correct operation of the project. Determine the production costs of the project, applying the relevant processes and indicators and Evaluate the profitability of the project. Through this, we begin to investigate several aspects such as the methodology that includes primary and secondary information, establishing as main methods: scientific, analytical, inductive, deductive and synthetic, as well as the main techniques of observation, interview and surveys. 5 Within the results achieved with the application of the Financial Indicators, it was determined that the Net Present Value is positive with a value of $ 7.165,332,22; an Internal Rate of Return of 16.75% higher than the rate expected by the partners (10,78%); in the sensitivity analysis based on the increase in costs with 14.38% with a sensitivity of 0.98 and decrease in income with 14.7% with a sensitivity of 0.83; which results in sensitivity less than 1; the Investment Recovery Period occurs in the sixth year, eleven months and fifteen days; The Cost-benefit Ratio is $ 4.27. Thus, these financial evaluators indicate the feasibility of the project to be created since all its results are positive according to the acceptance criteria of each one.